An International Perspective on Political Scandals - Weeber, Stan
This comparative study of political scandals in Italy, France, Spain, Japan, Russia and the United States led to the development of a sociology-based generalized stage model that is an initial step in explaining why scandals arise and how they are worked through and resolved. A crucial phase is the conflict phase between elites and masses, where potential scandals may die while others accelerate. The question of which events evolve to scandal and which do not is also likely to be worked through in this phase. The norm of reciprocity between officials and the public played a significant role in both scandal acceleration and scandal delimitation.economics and politics of scandals; comparative study; stage model of scandals; multi-theoretical approach